Analysis of public opinion on the regulation of euthanasia in Spain - García-Magna, Débora (My University, 2019)
The debate on the regulation of euthanasia has gone through several moments in the Spanish society and political landscape, showing up its strong ethical content. This is probably the reason why this crime has never been reformed since its inclusion in the penal code in 1995, despite the fact that in its almost 25 years of validity the code has been amended more than 30 times. Article 143.4 punishes the direct provocation of death in cases of serious illness that will lead to death, or that causes permanent and difficult to bear sufferings. The research presented is part of a larger study that seeks to analyze from both criminological, jurisprudential and dogmatic points of view the legislative initiatives on this issue (specially the last and not completed one, in 2018). Results from the first phase are now presented, including an analysis of the treatment of euthanasia by the mass media, and the public opinion on the subject. Data from the different questionnaires that have addressed the opinion of citizens on euthanasia are analyzed, highlighting some methodological limitations and the possible relationship of the results with the cases that have had a huge media coverage in Spain.
Keywords: Eutanasia; Opinión pública; Spanish criminal code; criminal law-making; mass media